Sperm ultrastructure of the honey bee (Apis mellifera) (L) (Hymenoptera, Apidae) with emphasis on the nucleus-flagellum transition region - Lino-Neto, José (2016)
The flagellum of Apis mellifera (Hymenoptera, Apidae) consists of two mitochondrial derivatives, an axoneme and two accessory bodies. The mitochondrial derivatives are of unequal size and lie parallel to the axoneme. In the larger derivative four regions can be distinguished while in the smaller, only three. The region occurring only in the larger derivative consists of paracystalline material. The smaller mitochondrial derivative terminates anterior to the larger one. An extremely long centriolar adjunct is observed between the nucleus and the smaller mitochondrial derivative. This adjunct is compact, very electron dense and gradually tapers from base toward apex, finishing at the anterior extremity of the axonemal microtubules. In this flagellar region, there is only one accessory body present between the larger mitochondrial derivative and the axoneme. Anteriorly, the tips of the axonemal microtubules are inserted in a well developed mass of granular appearance. This material surrounds the nuclear base, separating it from the anterior end of the larger mitochondrial derivative. We believe that the structure identified here as a centriolar adjunct is homologous to that observed in Formicidae, Ichneumonoidea and Symphyta. Therefore, very probably, it is common to most Hymenoptera.